PRAANGGAPAN DAN FUNGSI BAHASA PADA TUTURAN TOKOH DALAM FILM DZEEB KARYA NAJI ABU NOWAR - aziza, lady farah; Amatullah, Muna Nabila (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
This study aims to determine the types of presuppositions and what language functions contained in the speech of characters in the film Dzeeb. Researchers used a descriptive analysis method using the method of referencing which has the basis of tapping techniques. Based on the results of research on the first Dzeeb film, the utterances of the characters have four presuppositions, namely existential, lexical, factive, and non-active presuppositions. Existential presuppositions become findings that dominate the utterances of the characters in the film. Counterfactual presuppositions and structural presuppositions are not found in the speech of the characters in the Dzeeb film. The second is the function of language in speech utterances there are language functions including fatigue, directive, metalinguistic, and imaginative, referential functions. The directive language function is the finding that dominates the utterances of the characters in the Dzeeb film.